PENGARUH CSR SERTA AKTIVITAS CSR DALAM DIMENSI LINGKUNGAN, SOSIAL, DAN TATA KELOLA TERHADAP RISIKO FINANCIAL DISTRESS PADA PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Nonkeuangan yang Tercatat pada Bursa Efek Indonesia (BEI) Tahun 2018-2020) - Rafael Galih Cahyoputro; Paulus Th. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2022)
The objective of this study is to investigate the influence of corporate social responsibility, CSR in the environmental dimension, CSR in the social dimension, and CSR in the governance dimension on financial distress. The variables used in this study are CSR, CSR in environmental dimension, CSR in the social dimension, and CSR in the governance dimension as the independent variable, and financial distress as the dependent variable.This study uses a sample of 2018-2020 non-financial companies listed on the Indonesia Stock Exchange and Bloomberg Terminal with a total of 187 samples using purposive sampling with conditions that have already been determined. The analytical method in this study uses logistic regression analysis.The results of this study showed that CSR activities in the environmental dimension managed to have a negative effect on the company’s financial distress. While CSR itself has a positive significant on a company’s financial distress. In addition, there was no significant impact of CSR activities in the social dimension and CSR in the governance dimension on financial distress.